An Islamic Form of Logotherapy in the Treatment of Depression, Anxiety and Stress Symptoms in University Students in Iran - Fereydouni, Shapour (Journal of religion and health, 2022)
Previous research demonstrated that spiritually sensitive psychotherapy is an effective treatment for clients with depression or anxiety, with outcomes equivalent to secular control interventions. The goal of this study was to evaluate the efficacy of spiritually sensitive logotherapy intervention in the treatment of depression, anxiety, and stress symptoms in university students in Iran. Sixty students with elevated depression symptoms (Beck Depression Inventory II, BDI-II, 22 or greater) were randomly assigned to either a twelve-session group logotherapy programme or a control group. Results showed that spiritually sensitive logotherapy significantly reduced depression, anxiety, and stress, and significantly more so than in the control group (e.g. interaction effect for BDI-II: F = 56.8, p < 0.001, with a large effect size).